2015
DOI: 10.9734/bjmmr/2015/13124
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Metal Concentration in the Nails of Healthy and Cancer Patients Living in the Malwa Region of Punjab, India with a Random European Group – A Follow up Study

Abstract: The cancer prevalence in the Malwa region of Punjab (1089/million/year) is much higher than the national average cancer prevalence in India (800/million/year). In our previous study on hair metal analysis, we located a high metal burden in Punjabi cancer patients and their live-in relatives, suggesting that an excessive metal exposure is a factor in the pathogenesis of cancer. The present study focused on nail metal analysis, a biological material similar to hair. Previously, we had used BJMMR, 5(4): 480-498,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 96 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…It is likely that few studies have been conducted earlier because of the low [Sr] within fingernail clippings. The range of [Sr] in our group was from 0.011 to 0.110 μg g −1 , which was lower than the previously reported abundances in healthy adult fingernail clippings (0.54–1.0 μg g −1 ) . The lower [Sr] in our study may have resulted from our cleaning method, which was originally used for human scalp hair, and included an additional acetone and 0.1 M HCl wash that was not used in the other fingernail studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It is likely that few studies have been conducted earlier because of the low [Sr] within fingernail clippings. The range of [Sr] in our group was from 0.011 to 0.110 μg g −1 , which was lower than the previously reported abundances in healthy adult fingernail clippings (0.54–1.0 μg g −1 ) . The lower [Sr] in our study may have resulted from our cleaning method, which was originally used for human scalp hair, and included an additional acetone and 0.1 M HCl wash that was not used in the other fingernail studies.…”
Section: Discussionmentioning
confidence: 61%
“…These individuals may have increased [Sr] abundance compared with those without. Blaurock‐Bousch et al found that [Sr] differed between healthy European and Punjabi adults; while they did not specify what could be driving this difference, the presence of melanin could play a role.…”
Section: Discussionmentioning
confidence: 94%
“…As reported by Micro Trace Minerals Laboratory and some other scientific references, there are typically about 60 elements in the human fingernail [19][20][21]. Calcium, the structural element, is the most abundant mineral in the fingernail [19], as is in the body. In order to measure the concentration of calcium in the fingernail, due to the existence of a significant number of elements in this organ, the most appropriate method is calibration-based LIBS.…”
Section: Methodsmentioning
confidence: 95%
“…One can understand these cases as follows, because there no blood vessels in fingernail tissues so that the concentration of element Fe in fingernails of women with breast cancer can not similar to cancerous breast tumors. In researching metal exposure in the nails of the population at Punjab, India, Blaurock has shown that the concentration of element Fe in nails of breast cancer patients was much higher than to healthy people and intake Fe into the body due to environmental exposure 38 . Recently, it was not found any research for the evaluation of the concentration of element Zn in nails of women with breast cancer and healthy women.…”
Section: Discussionmentioning
confidence: 99%